A WEAK-(p, q) INEQUALITY FOR FRACTIONAL INTEGRAL OPERATOR ON MORREY SPACES VIA HEDBERG TYPE INEQUALITY - Idha Sihwaningrum; Hendra Gunawan (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2016)
By employing the growth measure, in this paper we prove the weak-(p, q) inequality for fractional integral operator on Morrey spaces via Hedberg type inequality. The proof also needs the weak-(p, p) inequality of the maximal operator in the same spaces.